Flavins and Flavoproteins in the Neuroimmune Landscape of Stress Sensitization and Major Depressive Disorder - Schrier MS; Smirnova MI; Nemeth DP; Deth RC; Quan N (Journal of Inflammation Research)
Matt Scott Schrier,1 Maria Igorevna Smirnova,2– 4 Daniel Paul Nemeth,1 Richard Carlton Deth,5 Ning Quan1,3 1Department of Biomedical Science, Charles E. Schmidt College of Medicine, Florida Atlantic University, Jupiter, FL, USA; 2The International Max Planck Research School (IMPRS) for Synapses and Circuits, Jupiter, FL, USA; 3Stiles-Nicholson Brain Institute, Florida Atlantic University, Jupiter, FL, USA; 4Department of Biological Sciences, Charles E. Schmidt College of Science, Florida Atlantic University, Jupiter, FL, USA; 5Department of Pharmaceutical Sciences, Barry and Judy Silverman College of Pharmacy, Nova Southeastern University, Ft. Lauderdale, FL, USACorrespondence: Matt Scott Schrier, Florida Atlantic University, Building: MC-17, Room: 229E, 5353 Parkside Drive, Jupiter, FL, 33458, USA, Email mschrier@health.fau.eduAbstract: Major Depressive Disorder (MDD) is a common and severe neuropsychiatric condition resulting in irregular alterations in affect, mood, and cognition. Besides the well-studied neurotransmission-related etiologies of MDD, several biological systems and phenomena, such as the hypothalamic-pituitary-adrenal (HPA) axis, reactive oxygen species (ROS) production, and cytokine signaling, have been implicated as being altered and contributing to depressive symptoms. However, the manner in which these factors interact with each other to induce their effects on MDD development has been less clear, but is beginning to be understood. Flavins are potent biomolecules that regulate many redox activities, including ROS generation and energy production. Studies have found that circulating flavin levels are modulated during stress and MDD. Flavins are also known for their importance in immune responses. This review offers a unique perspective that considers the redox-active cofactors, flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), as vital substrates for linking MDD-related maladaptive processes together, by permitting stress-induced enhancement of microglial interleukin-1 beta (IL-1β) signaling. Keywords: cofactor, cytokines, IL-1β, microglia, neuroinflammation, redox